Acceptance of technology among Malaysian fishermen - Mazuki, Raidah; Man, Norsida (Canadian Center of Science and Education, 2014)
This paper delves into research on acceptance of state-of-the-art in technology at the individual level among fishermen in Malaysia. This study is quantitative, and surveys a total of 200 registered fishermen from Johor, Malacca and Selangor. The analyses performed have confirmed that the main points that gear fishermen toward accepting fishery technology are related to the issues of safety, technological skill and knowledge, time saving, and minimization of interference by the middleman. A number of discussions and recommendations have been placed and can be expected to assist the relevant parties concerned with constructing strategies to further encourage the use of fishery technologies among fishermen in Malaysia.